Postwar nutritional status of lactating mothers: evidence from war-torn Tigray, Ethiopia - Gebrekiros Gebremichael Meles; Akeza Awealom Asgedom; Hailay Gebretnsae; Hagos Degefa Hidru; Abadi Kidanemariam Berhe; Gebregziabher Berihu Gebrekidan; Mengistu Hagazi Tequare; Mohamedawel Mohamedniguss Ebrahim; Yemane Berhane Tesfau; Haftom Gebrehiwot Woldearegay; Tedros Bereket; Gebru Hailu Redae; et al. (BMC, 2024)
Abstract Background Poor maternal nutrition is a significant public health problem, especially in conflict-affected areas. Lactating mothers are particularly vulnerable due to increased nutritional demands. The recent conflict in the Tigray region has resulted in serious crises and disruptions, worsening maternal undernutrition. Objective This study aimed to determine the post-war nutritional status of lactating mothers, in Tigray, Ethiopia, 2024. Methods A household-based cross-sectional study was conducted from January 16 to February 14, 2024, across six zones of Tigray, excluding the Western zone, which included 1245 lactating mothers with children under six months of age. Data were collected through a structured interview-based questionnaire designed in KoboToolBox. The collected data were managed and analyzed via Stata version 17 software. Descriptive statistics and bivariate and multivariable robust (modified) Poisson regression models were fitted to identify the factors associated with maternal undernutrition, after checking the necessary model assumptions. Adjusted prevalence rates with 95% confidence intervals were used as measures of effects and statistical significance. Results The prevalence of undernutrition among lactating mothers was 55.2% (95% CI: 52.3-58.1). The proportion of undernourished lactating mothers was greater in rural areas (60.7%: 57.3-64.0) than in urban (41.8%: 36.5-47.2). The factors independently associated with maternal undernutrition included elementary education [aPR (95% C.I): 1.1(1.01-1.3)], rural residence [aPR (95% C.I): 1.3(1.1-1.5)], iodized salt use [aPR (95% C.I): 0.9(0.8-0.99)], and low meal frequency [aPR (95% C.I): 1.3(1.2-1.5)]. Conclusions This study revealed a high maternal undernutrition prevalence among lactating mothers in Tigray in the post-conflict era. Therefore, interventions targeting educational opportunities, iodized salt use, and adequate meal frequency may help improve the nutritional status of lactating mothers in the conflict-affected areas in Tigray, Ethiopia.